PTH(1-84) replacement therapy for the treatment of hypoparathyroidism - Cusano, Natalie E (Expert Rev Endocrinol Metab, 2015)
Hypoparathyroidism is a rare disease characterized by hypocalcemia and insufficient circulating levels of parathyroid hormone (PTH). Conventional therapy includes calcium and active vitamin D supplementation, often in large doses. Therapy with calcium and vitamin D, however, does not address certain problematic aspects of the disease, including abnormal bone metabolism and reduced quality of life. Hypoparathyroidism is the only classic endocrine deficiency disease for which the missing hormone, PTH, is not yet an approved treatment. PTH(1-84) may soon become a therapeutic option for patients with hypoparathyroidism. PTH (1-84) has been demonstrated to maintain serum calcium while reducing or eliminating requirements for calcium and active vitamin D supplementation. Data from bone densitometry, bone turnover markers and histomorphometry of bone biopsy specimens show positive structural and dynamic effects on the skeleton. PTH replacement therapy may also be associated with improved quality of life. PTH(1-84) replacement therapy for hypoparathyroidism is promising, although further acquisition of long-term data is needed.